A Porous Mooncake‐Shaped Li4Ti5O12 Anode Material Modified by SmF3 and Its Electrochemical Performance in Lithium Ion Batteries. Issue 71 (9th November 2020) - Wang, Bo; Hu, Sisi; Gu, Lin; Zhang, Di; Li, Yazhao; Sun, Huilan; Li, Wen; Wang, Qiujun
Abstract: Reasonably designing and synthesizing advanced electrode materials is significant to enhance the electrochemical performance of lithium ion batteries (LIBs). Herein, a metal–organic framework (MOF, Mil‐125) was used as a precursor and template to successfully synthesize the porous mooncake‐shaped Li4 Ti5 O12 (LTO) anode material assembled from nanoparticles. Even more critical, SmF3 was used to modify the prepared porous mooncake‐shaped LTO material. The SmF3 ‐modified LTO maintained a porous mooncake‐shaped structure with a large specific surface area, and the SmF3 nanoparticles were observed to be attach on the surface of the LTO material. It has been proven that the SmF3 modification can further facilitate the transition from Ti 4+ to Ti 3+, reduce the polarization of electrode, decrease charge transfer impedance ( Rct ) and solid electrolyte interface impedance ( R se i ), and increase the lithium ion diffusion coefficient ( DLi ), thereby enhancing the electrochemical performance of LTO. Therefore, the porous mooncake‐shaped LTO modified using 2 wt % SmF3 displays a large specific discharge capacity of 143.8 mAh g −1 with an increment of 79.16 % compared to pure LTO at a high rate of 10 C (1 C=170 mAh g −1 ), and shows a high retention rate of 96.4 % after 500 cycles at 5 C‐rate. Abstract : The mooncake‐shaped Ti‐MOF was used as a template, and the mooncake‐shaped Li4 Ti5 O12 (LTO) was coated with SmF3 by using a coprecipitation method. Due to the fact that the mooncake morphology was maintained and to the successful growth of SmF3 on the surface, 2SmFLTO showed an excellent electrochemical performance.